STRATEGIES TO ENHANCE CRITICAL THINKING AND PROBLEM-SOLVING IN VOCATIONAL SCHOOLS - Anjani, Naila Desri; Marsofiyati; Wolor, Christian Wiradendi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to determine the influence of critical thinking skills and participation in extracurricular activities on students problem-solving ability at SMK Negeri 40 Jakarta. The research employed a quantitative method with a survey approach. The sample consisted of 72 respondents selected through non-probability sampling using the saturated sampling technique. Data were analyzed using multiple linear regression. The results show that critical thinking skills and participation in extracurricular activities simultaneously have a significant effect on students problem-solving ability, with a coefficient of determination (R²) of 58.7%. Partially, critical thinking skills significantly influence problem-solving ability, especially in the indicator of building basic skills. Participation in extracurricular activities also shows a significant influence, with mental engagement being the most dominant indicator. These findings support the theory that adequate critical thinking skills and consistent participation in extracurricular activities can enhance students ability to solve problems.